Strategic Factors of Household Solid Waste Segregation at Source Program, Awareness and Participation of Citizens of the 3 Municipality District of Tehran - Qasem Ghanbari; Shahnam Arshi; Mehdi Kamri; Maryam Soroush-Zadeh (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Solving the problems caused by household solid waste and its management without the continuous cooperation of the citizens as the main producers of household solid waste is impossible. The aims of this study were to define strategic factors of Household Solid Waste Segregation at Source Program and the level of awareness and participation of citizens in the program. Materials and Methods: In this cross-sectional study we interviewed 640 citizens of the 3 Municipality District of Tehran. Internal Factor Evaluation and External Factor Evaluation matrices were used to assess the strategic factors of the program. Results: Of 640 participants, 517 (80.8%) were aware of the program, and 383 (59.9%) participated in the program. Among participants 628 (98.1%) were well-informed about the correlation between implementation of the program and environmental health promotion. People between 35 to 45 years showed the most participation rate. Conclusion: This study showed that citizens showed acceptable awareness of the program and evaluation of internal and external factors indicated high potential to increase public participation in the program.